The Role of a Child Tax Policy: Population, Human Capital, and Economic Growth - Lyu, Chenmei (International Journal of Social and Administrative Sciences, 2022)
This study analyzes the impact of a child tax policy on the population, human capital, and economic growth in an overlapping generations model with endogenous fertility and human capital. The model shows that the child tax policy inhibits population growth and promotes human capital accumulation, generating a trade-off between the quantity and quality of children. The reduced population and increased human capital both contribute to per capita income. The balance between the negative impact of the child tax policy on the population and the positive impact on per capita income ultimately determines the impact on aggregate growth. The results show that the effect on aggregate growth rate is positive when parents' preference for children is large enough, and negative otherwise. In addition, with the pay-as-you-go pension system, I find that, under feasible conditions, the effect of the child tax policy on pensions is the same as that on total growth.